Injury patterns among female field hockey players - Murtaugh, K. (Medicine & Science in Sports & Exercise, 2001)
Purpose: To examine injury patterns among female field hockey players and to broaden the current base of knowledge by identifying the injury rates of different playing positions. It was hypothesized that goalkeepers would have the highest rate of injury, followed by forwards. Methods: High school, university, and national level female field hockey players (N = 158) completed an anonymous questionnaire. They reported personal characteristics (age, height, weight); field hockey information (level, years of experience, surface); injury history (type, site, cause, severity); and back pain information. Injury rates were calculated per athlete-year. Results: The most frequently injured site of the body was the lower limb (51%), followed by the head/face (34%), upper limb (14%), and torso (1%). The most prevalent types of injuries were ankle sprains, followed by hand fractures and head/face injuries. Goalkeepers had the highest rate of injury (0.58 injuries/athlete-year), whereas midfielders were the most injured field players (0.36 injuries/athlete-year). Back pain was reported by 59% of the sample, and the lower back was the most common site of this pain. Conclusion: There are differences in the rates of injury among playing positions in field hockey and in the types of acute injury sustained at each position. The high number of injuries to the head and face region is also cause for concern. Although most of these injuries are minor, the serious injuries that do occur can be very severe. Now that these patterns have been identified, further examination of the playing situations that lead to injury should be undertaken.